Effect of Morning vs Evening Strength Training on Sleep Quality in Young Healthy Adults: A Randomized Controlled Trial - Abhinandan C Y; Sushma S (RGUHS National Journal of Public Health)
Background Lack of quality sleep increases the risks of mortality cognitive impairment and depression. Pre sleep exercise can disrupt sleep onset as it can lead to high physiological excitement at bed time. Global exercise training guidelines suggest combining both strength and endurance training into training regimen to improve quality of sleep. There is an ongoing debate about the effects of morning versus evening training on sleep quality. The present study aimed to compare quality of sleep among morning and evening strength and endurance trainers.Aims and Objectives To assess quality of sleep using a sleep questionnaire in the morning and evening strength and endurance training groups before and after an intervention and to compare the quality of sleep between the groups.Methods The study was conducted among 80 healthy young adults in the age group of 18ndash30 years who were previously not involved in regular physical activity. They were randomly divided using simple randomization into morning and evening training groups. Subjects included in both the morning and evening groups performed strength and endurance training. The quality of sleep was assessed using Pittsburgh Sleep Quality Index PSQI in morning and evening groups before and after a four-week intervention period. Intergroup comparisons were analysed using relevant statistical tests.Results The data collected were analysed using Student t test. The P value for Global PSQI score was found to be statistically significant P lt0.05 in the evening training group and highly significant P lt0.01 in the morning training group.Conclusion Though both morning and evening exercise proved to improve quality of sleep morning strength training was found to be more beneficial towards improving the quality of sleep sleep initiation and prolongation when compared to evening exercise.